Pengembangan Media Pembelajaran Flipbook Berbasis Keteladanan Walisongo untuk Meningkatkan Pemahaman Siswa MA Mambaul Ulum - Febrianti, Arista Sasa Bela; Rahmawati, Rina Dian (Lembaga Yasin AlSys, 2025)
This research is motivated by the lack of innovation in the use of learning media in schools. Monotonous learning without media variations can cause boredom in students, resulting in less than optimal understanding of the material. Flipbooks, as an interactive learning medium, are expected to improve the quality of learning and provide a more interesting and effective learning experience. This research aims to develop flipbook-based learning media on Walisongo's exemplary material at MA Mambaul Ulum Megaluh Jombang. This study measures the validity and feasibility of media products by involving material experts and media experts, as well as evaluating the responses of teachers and students to the products developed. The research method used is R&D (Research and Development) with a 4D development model, namely Define, Design, Development, and Disseminate. Data was obtained through interviews, questionnaires, and documentation. The results of the study show that the flipbook learning media product developed has been validated with a score of 86% by material experts and 83% by media experts, both of which are in the